Natural Bond Orbital Analysis of [Fe(H2O)6]2+/3+ and [Zn(H2O)6](H2O)N2+;N=0-4 - Pokhrel, Nabaraj; Lamichhane, Hari Prasad (Journal of Institute of Science and Technology, 2018)
Nature of delocalization of the electrons from the ligands to metals in the first coordination sphere of the high-spin complexes [Fe(H2O)6]2+/3+ and [Zn(H2O)6]2+ are computationally studied using density functional theory. Among the studied complexes, natural charge transfer from H2O ligands to metal ion is found to be maximum of 1.556e in [Fe(H2O)6]3+ and minimum of 0.621e in [Zn(H\2O)6]2+. On the other hand, the interaction between the lone pairs of oxygen with metal ion was found to be stronger in [Zn(H2O)6]2+ than in the complexes with second coordination sphere. Number of such strong interactions in the first coordination sphere was found to be decreased with the addition of H2O ligands in the second coordination sphere. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 148-155